Pengabaian Penerapan Pasal 1245 KUH Perdata, Force Majeure pada Masa Pandemi Covid-19 - Vera Wheni Setijawati Soermawi; Merri Lutfiyah Amelia (Syntax Literate, 2023)
The Covid-19 pandemic that has occurred since 2019 has hit all countries in the world. The impact experienced by every country, including Indonesia, is the decline in the health of its citizens due to being infected with the Corona virus. Declining economic capacity results from the implementation of restrictions on social, economic activities of the state and its citizens as well as the security of state border areas (Abron, 2021). These three impacts are not considered as Force Majeure conditions in the Airmadidi District Court Decision Number: 11/Pdt.G.S/2021/PN Arm (a quo decision). The debtor's inability to pay multipurpose installment payments as a result of the implementation of restrictions on social and economic activities is not considered as a force majeure. This study will examine the decision a quo by applying a socio-legal studies approach. The purpose of this research is to provide legal certainty in the application of Force Majeure in default cases